ARTIFICIAL INTELLIGENCE AND ITS ROLE IN HUMAN RESOURCES MANAGEMENT - Hasan Fadhil AL-Thabhawee (ZILLZELL MEDIA PRIMA, 2025)
This study reveals the definition of human resource management by examining definitions proposed by various theorists and attempting to arrive at new definitions. Previous studies have identified several benefits that can be achieved through the use of human resource management within an organization. In this study, partial least squares structural equation modeling (PLS-SEM) was used in statistical software (Smart PLS, version 4.0.8.9) to analyze data and measure the role of artificial intelligence in human resource management at Najaf International Airport, serving 120 employees. The results of this study showed that artificial intelligence plays a role in human resource management at Najaf International Airport. The study’s key recommendations include linking employee incentives for this new technological skill (artificial intelligence) with employee learning if Najaf International Airport aims to enhance the adoption of new working methods.